Review: Analysis of lead level in the blood of several professions in Indonesia - Rizal, Fahmi (Asian Journal of Health and Applied Sciences, 2022)
Lead is a toxic heavy metal found in the environment. Lead is an abundant, important, and dangerous element. In addition, lead cannot be decomposed, so it easily accumulates in the environment and causes poisoning. Lead poisoning is a condition when a person experiences lead deposition in the body. Lead is a metal-shaped chemical element with a very high toxic content. Lead toxins can affect the function of human organs and systems. A person can experience serious health problems if exposed to small amounts of lead for a long time. It can even be fatal if the level of lead exposure is very high. Lead exposure is particularly dangerous for workers who are directly or indirectly related to it. Therefore, there needs to be an in-depth analysis of lead exposure among some professional workers in Indonesia. The method used in this research is an observational study using a cross-sectional approach and laboratory analysis using Atomic Absorption Spectrophotometry (AAS). Based on the research that has been done, it is found that the level of lead (Pb) in the blood of some workers in Indonesia is still below the threshold because it is in accordance with Decree of the Minister of Health of the Republic of Indonesia Number 1406/MENKES/SK/IX/2002 concerning Standards for Examination of Pb Levels in Human Biomarker Specimens that the content of lead (Pb) is 0.1–0.25 µg/ml.